Photon-induced spin transport in two-dimensional electron systems - Korostil, A. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
We study spin-dependent transport in a two-dimensional electron gas subject to an external step-like potential V(x) and irradiated by an electromagnetic field (EF). In the absence of EF the electronic spectrum splits into spin sub-bands originating from the "Rashba" spin-orbit coupling. We show that the resonant interaction of propagating electrons with the component EF parallel to the barrier induces a nonequilibrium dynamic gap (2ΔR ) between the spin sub-bands. Existence of this gap results in coherent spin-flip processes that lead to a spin-polarized current and a large magnetoresistance, i.e. the spin valve effect. These effects may be used for controlling spin transport in semiconducting nanostructures, e.g. spin transistors, spin-blockade devices etc., by variation of the intensity S and frequency ω of the external radiation.